SENSEX- The Dancing Beauty of Indian Stock Market - Chittedi, Krishna Reddy (Indian Journal of Finance, 2009)
Stock market indices are the barometer of the stock market. They mirror the stock market behavior and the broad trends in the markets. The SENSEX compiled in 1986 was calculated on a "Market Capitalization-Weighted" methodology of 30 component stocks representing large, well established and financially sound companies across key sectors. SENSEX crossed the twenty thousand mark cheering thousands of investors in the recent Bull Run. Sensex took a little over 20 years to reach the first 10,000 mark, but just a little over 20 months to double that score. The rise in global market and expectations of increased foreign portfolio investment has driven traders’ interest in the market. It is a broad based movement and the major gainers are front line stocks. On that historical date as many as 29 shares that comprise 30 share index ended higher except the Wipro Limited, which experienced a marginal decline of 0.2%. In this 10k march, not only the Nifty and the Sensex stocks the midcaps and small caps have also gained. They gained by 2.2% and 2.7% respectively during that peak. A buoyant economy provided a firm underpinning to mid-cap companies. The FIIs have broadened their investment in more than 750 stocks and in the several mid-cap companies, they are holding over 20 per cent. Institutional investors and FIIs have provided a perfect support to the rising equity values.